Integrasi Agama dan Sains Menurut Ian G. Barbour dan Sumbangannya terhadap Kajian Keislaman (Tsamratul Fikri | Jurnal Studi Islam, 2022)
The conflict between science and religion continues because it is considered two different areas. The relationship between science and religion is a complicated but important one. Science holds the realm of reasoning, while religion is in the realm of revelation. At the same time, both are actively involved in solving the problems of human life. This paper raises the contribution of Ian G. Barbour's thoughts in his fourth typology, namely integration and how it contributes to Islamic studies.